Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có:+)f(2017)=ax^3 + bx +5=5
x(ax^2 + bx)=0
=>ax^2 + bx=0(do x=-2017)
+)f(-2017)=ax^3 + bx +5
=x(ax^2 +bx)+5
=x.0+5=0+5=5
Ta có :
\(f\left(0\right)=a.0^2+b.0+c=c=2015\)
\(f\left(1\right)=a.1^2+b.1+c=a+b+c=2016\)
\(f\left(-1\right)=a.\left(-1\right)^2+b.\left(-1\right)+c=a-b+c=2017\)
\(a+b+2015=2016\Rightarrow a+b=1\)
\(a-b+2015=2017\Rightarrow a-b=2\)
Cộng vế với vế ta được :\(\left(a+b\right)+\left(a-b\right)=1+2\)
\(\Leftrightarrow2a=3\Rightarrow a=\frac{3}{2}\)
\(\Rightarrow\frac{3}{2}+b=1\Rightarrow b=1-\frac{3}{2}=-\frac{1}{2}\)
\(\Rightarrow f\left(-2\right)=\frac{3}{2}.\left(-2\right)^2+\left(-\frac{1}{2}\right).\left(-2\right)+2015\)
\(=\frac{3}{2}.4+1+2015\)
\(=6+1+2015\)
\(=2022\)
Vậy \(f\left(-2\right)=2022\)
\(f\left(1\right)=a_{2017}+a_{2016}+...+a_3+a_2+a_1+a_0\)
\(f\left(-1\right)=-a_{2017}+a_{2016}+...-a_3+a_2-a_1+a_0\)
\(f\left(1\right)+f\left(-1\right)=2\left(a_{2016}+a_{2014}+...+a_2+a_0\right)\)
\(S=\frac{f\left(1\right)+f\left(-1\right)}{2}=\frac{3^{2017}+1}{2}\)
\(P\left(x\right)=x^{2017}-2018x^{2017}+2018x^{2016}-...-2018x+1\)
Vì \(x=2017\)
\(\Leftrightarrow x+1=2018\)
Thay vào P(x) ta được :
\(P\left(x\right)=x^{2017}-x^{2017}\left(x+1\right)+x^{2016}\left(x+1\right)-...-x\left(x+1\right)+1\)
\(P\left(x\right)=x^{2017}-x^{2018}-x^{2017}+x^{2017}+x^{2016}-...-x^2-x+1\)
\(P\left(x\right)=-x^{2018}+1\)
\(P\left(x\right)=-2017^{2018}+1\)
Ta có : P(2017)=(a20175+b2017)+24=18
⇔ (a20175+b2017)= -6
Lại có : P(-2017)=a(-2017)5+b(-2017)+24=-a20175-b2017+24
= - (a20175+b2017)+24
Hay : -(-6)+24=6+24=30
Vậy : P(-2017)=30